Food production strategies for improving household food security amidst rising food prices: sharing the Malaysian experience - Khor, Geok Lin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2008)
Food and fuel prices have soared in recent years affecting most adversely the poor and those with fixed incomes. Since 2000, wheat price in the international market has more than tripled and maize prices have more than doubled. The price of rice, the staple of billions in Asia, has tripled in the past year. The surge of food prices has been blamed on multiple factors including higher energy and fertilizer costs, greater global demand, drought, the loss of arable land to biofuel crops, and price speculation. In light of the spiraling rise in food prices, there is the prospect of increasing rates of under-nutrition worldwide. As it is, 800 million are estimated to be suffering from chronic malnourishment, with another 2.1 billion people living close to subsistence levels on less than US$2 a day. Some perspectives of the food production experience of Malaysia are shared here as a case of a country that has built up capabilities and resources through high level of foreign and domestic investment leading to a diversified economy. In response to the recent surge in the price of rice, the Malaysian government announced the setting up of a dedicated fund amounting to US$1.25 billion to increase production of food including fruits and vegetables, and targeting 100% self-sufficiency in rice, by growing rice on a massive scale in Sarawak. During the current five-year development plan for the period of 2006-2010, (Ninth Malaysia Plan), the role of the agriculture sector is considerably enhanced to be the third pillar of economic growth, after manufacturing and services. Among the measures taken, are those aimed at increasing incomes of smallholders and fishermen mainly through improving productivity. These measures include encouraging more rice farmers to participate in mini-estates and group farming, providing financial assistance to rehabilitate cocoa, pepper and sago smallholdings, enhancing the capabilities of coastal fishermen, and setting up of a special program to assist poor households in the agriculture sector to diversify their sources of income. The various socio-economic programs in Malaysia that have been put in place over the years may have cushioned to some extent so far the severity of the dramatic hikes in food prices.